(untitled) (Research, Society and Development, 2022)
Salicylic acid has one of its characteristics the allelopathic potential. The present paper, is a research quantitative in nature aimed to assess the allelopathic potential of salicylic acid to identify the best concentration range for other pure substances. The bioassays were performed in a BOD incubator, seeking to assess the seedling growth by measuring the radicle and hypocotyl length. Each bioassay occurred for 12 days. The concentrations of salicylic acid used in the bioassays were: 1000, 750, 500, 250, 125, and 62.5 ppm and control. The obtained data were submitted to the tests: Kolmogorov-Smirnov normality, the two-way ANOVA with repetition, and Tukey. Based on the results obtained, it was possible to observe that several concentrations demonstrated significant differences, i.e., there is an allelopathic activity in both species (Euphorbia heterophylla and Bidens pilosa). The highlights were for the concentrations of 750 and 1000 ppm for E. heterophylla and 500, 750 and 1000 ppm for B. pilosa. However, there was no significant difference between these concentration groups. The radicle’s length was the part most negatively affected. These results can be used to identify better concentrations for other pure substances, which are usually obtained in small quantities, being useful in the formulation of a product with characteristics of bio-herbicides.